2013
DOI: 10.1097/opx.0b013e318278fc44
|View full text |Cite
|
Sign up to set email alerts
|

Refractive Stabilization and Corneal Swelling After Cataract Surgery

Abstract: Automated refraction is highly repeatable and can be used to monitor postsurgical refractive changes. Whereas corneal swelling becomes stable 2 weeks after cataract surgery, automated refraction becomes stable after 1 week and can be used to accurately prescribe corrective lenses at that time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
46
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 30 publications
4
46
0
Order By: Relevance
“…; de Juan et al. ). This early shift may be related to changes in anterior chamber depth and IOL position within the eye.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…; de Juan et al. ). This early shift may be related to changes in anterior chamber depth and IOL position within the eye.…”
Section: Discussionmentioning
confidence: 98%
“…from ; both spherical refraction and cylinder refraction were stable after 1 week, even though the corneal swelling significantly continued to diminish past the first week after surgery (de Juan et al. ). In our study, the amount of cylinder refraction was not stable after 1 week.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2] Researchers demonstrated that automated refraction becomes stable one week after the phacoemulsification and can be used to prescribe corrective lenses at this time. [3]…”
mentioning
confidence: 99%
“…Most of those studies were retrospective and evaluated the spherical equivalent, but it is more accurate to distinguish between spherical and cylindrical refraction. In a prospective study, we found that refraction (spherical and cylindrical component) was stabilized one week after surgery [6]. Nevertheless, we caution about the general applicability of our findings.…”
Section: Institute Of Applied Ophthalmobiology (Ioba-eye Institute) mentioning
confidence: 45%